FBG as a Medical Thermometer - Amal Ibrahim Mahmood (Journal of Madenat Alelem University College, 2016)
An FBG thermometer was designed for medical applications in human body. In this work, a short period Fiber Bragg Grating (FBG) temperature sensor system were demonstrated and investigated according to the measurement of the Bragg wavelength shift. This FBG designed by using OptiGrating 4.2 software and various temperature where applied according to human body temperature ranging from hypothermia (35 ̊C) to hyperthermia (42 ̊C) and taking into consideration the normal human body temperature as (37 ̊C) which is taken as a reference temperature in the simulation design. There was shifting in Bragg wavelength for each temperature degree. The applied temperature of FBG was so small so the strain effect is neglected.